Mededingende politieke paradigmas oor die Grensoorlog 1966-1989 - Venter, Albert (Faculty of Humanities, University of the Free State, 2009)
In this essay the author identifies five political paradigms with which the Border War was analysed, criticised, attacked and/or legitimised. Making explicit use of the insights of Thomas Kuhn, the following paradigms were selected the total onslaught, the liberal opposition analysis, the struggle critique, the technicist analyses and lastly the radical critique. The essay concludes that all the paradigms had a more or less underlying political agenda. The total onslaught legitimised the border conflict on Cold War grounds as a struggle against world communist domination. Its main anomaly was the apartheid state that it could not defend. The liberal critique showed the anomalies of the apartheid paradigm but could not convince the white electorate of its merits. The struggle paradigm defends the armed struggle on moral grounds, but could not escape the anomalies of its Soviet and Marxist backers. The technicists, while critical of apartheid, maintained their defence on mainly Western Cold War terms. The anomaly here was that it had to ignore or dampen down the apartheid background to the war. The radical analysts, while maintaining a sophisticated social science critique, could not escape their underlying political goal that the apartheid regime was illegitimate and had to go. While some of the paradigms have been discredited, such as apartheid total onslaught, the understanding of the Border War in moral terms is still controversial and sustains the problematic of contending paradigms that paradigms tend to be mutually incomprehensible. The essay also highlights the seriousness of contending intellectual constructs that academic paradigms can also, and indeed often do, legitimise violence and warfare. They are not simply scholarly games.
Keywords: Western Cold War; Border War; Political paradigms; Struggle critique; Political agenda